Nem palácio, nem ninho: um lugar para a criança e o adolescente no sistema de justiça - Faria, Cybelle Saad Sabino de Freitas (2018)
The path to be followed by the child and / or adolescent victim of violence is perverse and victimizing. In the justice system they face the same obstacles as adults in addition to facing barriers and impediments linked to their vulnerability. The new law 13.431, which comes into force in April 2018, determines new conduct in the relationship of justice with the child and adolescent public. Their reception and care should be conducted in a friendly environment, separate from the Hearing Room, especially designed to promote their psychological protection. However, in the legal area, it is not specified how these sites should be, in the architectural scope subjective parameters for planning such spaces are not observed and within the scope of the administration of justice there are difficulties linked to the lack of long term planning, resources and bureaucratic obstacles. In the buildings chosen as object of study, the Criminal Forum and the Juvenile Court of Children and Youth, both located in the city of Goiânia, were identified inadequacies and possibilities. The objective of this study is to identify the desirable material and immaterial qualities in the environments for the care of children and adolescents who participate in the procedures of justice through the study of physical, psychoemotional and symbolic-cultural needs, desires and values ​​alluding to this age group. As a result, the study provides guidelines for new configurations of judicial spaces for children and adolescents based on objective and subjective aspects.